Strategic management to increase crop yields in Krandon Village - Nofikasari, Nofikasari; Sari, Tiwi Punden; Ambarsari, Arum; Purwanto, Edy (Community Empowerment, 2025)
The purpose of this community service is to provide guidance on strategic management to improve agricultural yields for the Farmer Group in Ketanon Hamlet. The implementation of the activities was carried out in several stages, namely the preparation stage aimed at observing problems, the implementation stage which included outreach on the methods and importance of strategic management, and the evaluation stage which was measured based on the presence or absence of an increase in crop yields. To improve agricultural yields, strategic management efforts in agricultural planning, resources, finance, production, and marketing are needed. This strategic management outreach has been proven to significantly increase the crop yields of the Ketanon Hamlet farmer group from 21,600 kg in 2023 to 36,000 kg in 2024.